Mechanisms of persistent atrial fibrillation and recurrences within 12 months post-ablation: Non-invasive mapping with electrocardiographic imaging - Vijayakumar, Ramya; Faddis, Mitchell N.; Cuculich, Phillip S.; Rudy, Yoram (Frontiers in Cardiovascular Medicine, 2022)
Introduction Catheter ablation of persistent AF has not been consistently successful in terminating AF or preventing arrhythmia recurrences. Non-invasive Electrocardiographic Imaging (ECGI) can help to understand recurrences by mapping the mechanisms of pre-ablation AF and comparing them with the patterns of recurrent arrhythmias in the same patient. Methods Seventeen persistent AF patients underwent ECGI before their first catheter ablation. Time-domain activation maps and phase progression maps were obtained on the bi-atrial epicardium. Location of arrhythmogenic drivers were annotated on the bi-atrial anatomy. Activation and phase movies were examined to understand the wavefront dynamics during AF. Eight patients recurred within 12 months of ablation and underwent a follow-up ECGI. Driver locations and movies were compared for pre- and post-ablation AF. Results A total of 243 focal drivers were mapped during pre-ablation AF. 62% of the drivers were mapped in the left atrium (LA). The pulmonary vein region harbored most of the drivers (43%). 35% of the drivers were mapped in the right atrium (RA). 59% (10/17) and 53% (9/17) of patients had repetitive sources in the left pulmonary veins (LPV) and left atrial appendage (LAA), and the lower half of RA, respectively. All patients had focal drivers. 29% (5/17) of patients had macro-reentry waves. 24% (4/17) of patients had rotors. Activation patterns during persistent AF varied from single macro-reentry to complex activity with multiple simultaneous wavefronts in both atria, resulting in frequent wave collisions. A total of 76 focal driver activities were mapped in 7/8 patients during recurrence. 59% of the post-ablation AF drivers were mapped in the LA. The pulmonary vein region harbored 50% of total drivers. 39% of sources were mapped in the RA. AF complexity remained similar post-ablation. 58% (44/76) of pre-ablation sources persisted during recurrence. 38% (3/8) of patients had macro-reentry and one patient had rotors. Conclusion ECGI provides patient-specific information on mechanisms of persistent AF and recurrent arrhythmia. More than half pre-ablation sources repeated during post-ablation recurrence. This study provides direct evidence for drivers that persist days and months after the ablation procedure. Patient-tailored bi-atrial ablation is needed to successfully target persistent AF and prevent recurrence. ECGI can potentially predict recurrence and assist in choice of therapy.